Impact of coronavirus disease 2019 (COVID-19) pre-test probability on positive predictive value of high cycle threshold severe acute respiratory coronavirus virus 2 (SARS-CoV-2) real-time reverse transcription polymerase chain reaction (RT-PCR) test results. (9th September 2022) - Gubbay, Jonathan B.; Rilkoff, Heather; Kristjanson, Heather L.; Forbes, Jessica D.; Murti, Michelle; Eshaghi, AliReza; Broukhanski, George; Corbeil, Antoine; Fittipaldi, Nahuel; Hopkins, Jessica P.; Kristjanson, Erik; Kus, Julianne V.; et al.
Abstract: Objectives: Performance characteristics of SARS-CoV-2 nucleic acid detection assays are understudied within contexts of low pre-test probability, including screening asymptomatic persons without epidemiological links to confirmed cases, or asymptomatic surveillance testing. SARS-CoV-2 detection without symptoms may represent presymptomatic or asymptomatic infection, resolved infection with persistent RNA shedding, or a false-positive test. This study assessed the positive predictive value of SARS-CoV-2 real-time reverse transcription polymerase chain reaction (rRT-PCR) assays by retesting positive specimens from 5 pre-test probability groups ranging from high to low with an alternate assay. Methods: In total, 122 rRT-PCR positive specimens collected from unique patients between March and July 2020 were retested using a laboratory-developed nested RT-PCR assay targeting the RNA-dependent RNA polymerase (RdRp) gene followed by Sanger sequencing. Results: Significantly fewer (15.6%) positive results in the lowest pre-test probability group (facilities with institution-wide screening having ≤3 positive asymptomatic cases) were reproduced with the nested RdRp gene RT-PCR assay than in each of the 4 groups with higher pre-test probability (individual group range, 50.0%–85.0%). Conclusions: Large-scale SARS-CoV-2 screening testing initiatives among low pre-test probability populations should be evaluated thoroughly prior to implementation given the risk of false-positive results and consequent potential for harm at the individual and population level.